Elucidation of Biochemical Pathways Underlying VOCs Production in A549 Cells - Furuhashi, Takeshi; Ishii, Ryuga; Onishi, Haruka; Ota, Shigenori (Frontiers in Molecular Biosciences, 2020)
Cellular volatile organic compounds (VOCs) are unique compounds whose metabolic pathways remain enigmatic. To elucidate their metabolism, we investigated the VOCs of lung cancer A549 and 2 non-cancer lung cells (HLB; HBEpC). Neutral sugars and lactate in the medium were measured by colorimetric assay. VOCs were enriched by monotrap and profiled by GC-MS. To investigate the enzymes that change VOC metabolism in cells, we conducted ALDH activity assays and qPCR. ROS (reactive oxygen species) assays were conducted to assess oxidation stress. The colorimetric assay showed that especially A549 and HLB took up sugars from the medium and rapidly secreted lactate into the medium. The VOC profile (GC-MS) revealed a trans 2-hexenol increase, especially in A549 lung cancer cells. This is a novel lipid peroxidation product from animal cells. Based on the absolute quantification data, trans 2-hexenol increased in parallel with number of A549 cancer cells incubated. The qPCR data indicate that ADH1c plays an important role in the conversion into trans 2-hexenol.